2014
DOI: 10.1074/jbc.m113.523019
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Map of Bromodomain Protein 4 (BRD4) Interactions with the Histone H4 Tail and the Small Molecule Inhibitor JQ1

Abstract: Background: BRD4 is a reader of acetylated histones.Results: Mutational analysis of BRD4 BD1 allowed the identification of three groups with different binding profiles.Conclusion: Pro-82, Leu-94, Asp-145, and Ile-146 have a differentiated role in acetyl-lysine and inhibitor interaction.Significance: Identification of residues essential for BRD4 function will guide the design of novel inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
132
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 66 publications
10
132
0
5
Order By: Relevance
“…Indeed, the EC 50 values of JQ1 for the mutant BRD4 variants in our cellular assay matched well with the affinities obtained in biochemical and biophysical assays performed with these mutants. 12 Moreover, we showed that the loss of stabilization induced by JQ1 for each mutant was similar to the loss of binding affinity of BRD4 to acetylated H4 peptide and that the highest impact was found with mutants Y97F and N140A. These residues are known to recognize acetylated histones by forming direct (N140) and watermediated (Y97) hydrogen bonds with acetylated peptides and to interact with inhibitors mimicking acetyl-lysines such as JQ1 and I-BET-762.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, the EC 50 values of JQ1 for the mutant BRD4 variants in our cellular assay matched well with the affinities obtained in biochemical and biophysical assays performed with these mutants. 12 Moreover, we showed that the loss of stabilization induced by JQ1 for each mutant was similar to the loss of binding affinity of BRD4 to acetylated H4 peptide and that the highest impact was found with mutants Y97F and N140A. These residues are known to recognize acetylated histones by forming direct (N140) and watermediated (Y97) hydrogen bonds with acetylated peptides and to interact with inhibitors mimicking acetyl-lysines such as JQ1 and I-BET-762.…”
mentioning
confidence: 90%
“…We selected W81, P82, Y97, N140, and M149 as mutational sites for this study, in view of their role in the recognition by acetylated histone peptides and JQ1. 12 In total, 48 small molecules were tested against wild-type and five different mutant BRD4 BD1 constructs.…”
Section: Impact Of Brd4 Bd1 Mutations On Intracellular Stability Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Thet etra-acetylated histone H4-mimicking peptide H4 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] [36] and 4.8 mm (ITC). [38] BRD4 (1) can recognize two adjacent KAc residues on the same peptide at any one time. [39] X-ray crystal structures reveal the N-terminal KAc forms ah ydrogen-bonding interaction with the conserved asparagine residue,w hile flexible glycine residues allow ap eptide conformation where the C-terminal KAc fits into the grooves created by the ZA and BC loops (PDB:3 UVW,3 UVX, 3UVY).…”
mentioning
confidence: 99%
“…BRD4 binds Kac of histone via its bromodomains, and then recruits the positive transcription elongation factor b (P-TEFb), which is a heterodimer of cyclin-dependent kinase 9 (CDK9) and its regulator cyclin T, to the transcription start site, leading to transcription elongation through phosphorylation of the carboxyl-terminal of RNA polymerase II. [11][12][13] BRD4 therefore acts as a transcriptional coactivator of many cellular genes. For example, the interaction of BRD4 with P-TEFb promotes G 1 gene expression and cell cycle progression.…”
Section: Features Of Bet Family Proteinsmentioning
confidence: 99%